Fire Effect on Population of Soil-Inhabiting Nematodes in Clouds Forest, Shahrud, Iran - Abdoos, Hamid Reza; Saeedizadeh, Ayatollah (Indian Forester, 2017)
Nematodes are so abundant and omnipresent in ecosystems, hence they serve as elegant indicators of environmental disruption, including fire. The effect of fire on nematode population was studied in the soil of Clouds Forest, Shahrud, Iran. For the purpose, 100 soil samples of burned and unburned areas from the depth of 20cm were taken for two times (1 and 13 months after the fire) randomly. Nematodes were collected using sieves, and according to centrifuge method. The results showed the population of nematodes, genera Acrobeles, Discolaimus, Mylonchulus, Amplimerlinius, Aphelenchus, Criconemoides, Nagelus, Helicotylenchus, Xiphinema, Filenchus, Crossonema, Rotylenchus, Psilenchus and Aphelenchoides, decreased in the soil burned compared with unburned soil at one month after the fire. The most of reducing the population was obtained in plant-associated, predator, omnivore, plant parasite, bacteriovore and f ungivore nematodes in burned soil, respectively. The population experienced higher than increase in the 13 months after a fire in predator, plant parasite, bacteriovore, omnivore, plant-associated and fungivore nematodes, respectively (pâ‰¤0.05).